STATIC ANALYSIS OF A BAND SAW SHAFT BY FEM (Innovation in Woodworking Industry and Engineering design, 2026)
A static analysis of the main shaft of a universal band saw with two bearing supports, a console drive side wheel and console V-belt pulley is carried out by the method of finite elements (FEM) with Autodesk Inventor Professional. The 3D model of the band saw shaft is generated with all elements of the real shaft – keyslot, grooves for clip ring, centre holes, chamfers, filets, and etc. Two variants of loading are set: first for vertical V-belt transmission and second for horizontal V-belt transmission. Stresses, strains, displacements and factor of safety distributions are obtained and visualized in the 3D model of the band saw shaft for these variants. The effected differences in the static strength of band saw shaft are analyzed.